Omission of axillary dissection after a positive sentinel lymph-node: Implications in the multidisciplinary treatment of operable breast cancer. (July 2016) - Ponzone, Riccardo; Ruatta, Fiorella; Gatti, Marco; Castellano, Isabella; Geuna, Elena; Amato, Giulia; Kubatzki, Franziska; Sgandurra, Paola; Sapino, Anna; Montemurro, Filippo
Highlights: The number of metastatic axillary nodes is a prognostic factor in breast cancer. Axillary dissection can be omitted in some women with a positive sentinel biopsy. Lack of information on the axillary burden may influence adjuvant treatment choices. Omission of axillary dissection involves a multidisciplinary decision process. Abstract: Omission of axillary dissection in women with breast cancer and one or two positive sentinel-node biopsy is a major advancement in the management of this disease. Supported by a sound rationale and confirmed by prospective, randomized trials, omission of axillary dissection is now recommended in women who have undergone breast conserving surgery and who are candidate to adjuvant radiotherapy. Because breast cancer is best managed in the context of a multidisciplinary team, this surgical shift in the paradigm is expected to have implications that extend also to the other specialties involved in the team. In fact, the full evaluation of the axillary tumor burden has been historically considered an essential part of tumor staging and the absolute number of involved node critical information to tailor post-surgical treatments. Lack of this information in a patient with axillary involvement documented by a positive sentinel lymph-node biopsy may represent a challenge when deciding on further, post-surgical treatments. This review will address the critical aspects and the potential implications of omission of axillary dissection in the context of the multidisciplinary breast team.